Investigation on the internal and external validity of the antisocial subscale of the dimensional clinical personality inventory 2 - Magarotto Machado, Gisele (The journal of forensic psychiatry & psychology, 2021)
This study aimed to verify Dimensional Clinical Personality Inventory 2 (IDCP-2) factors to identify ASPD traits, proposing an ASPD subscale for IDCP-2 (IDCP-ASPD). The sample consisted of 460 Brazilian adults, where 367 were a community sample (aged 18–63 years), and 93 prison inmates (aged 18–62 years). The participants answered IDCP-2 factors, Personality Inventory for DSM-5 (PID-5) facets, and the Affective resonance factor of the Affective and Cognitive Measure of Empathy (ACME). The IDCP-ASPD factors showed high associations with the PID-5 facets. We found a structure of three factors for the IDCP-ASPD: Affective, Interpersonal, and Lifestyle. The IDCP-ASPD factors showed a good discriminatory capacity for the groups of offenders and non-offenders, and the groups with high and low scores in the ASPD features. The exception was the Seduction and Manipulation factor, which presented a non-significant difference between the offenders and non-offenders groups. The factors of the IDCP-ASPD showed good performance. However, Antagonism, Impulsivity, Deceitfulness, and the higher-order factor Lifestyle prove to be the bests to identify people with elevation on ASPD traits. The factors of the IDCP-ASPD demonstrated usability for screening typical ASPD features.